2018
DOI: 10.1007/s10517-018-3978-0
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-I Stimulates Cell Proliferation in Bone Marrow Cell Culture

Abstract: Culturing of bone marrow cells in serum-free RPMI-1640 medium led to a decrease in the rate of DNA biosynthesis. Addition of HDL or their main protein component apolipoprotein A-I to the culture medium dose-dependently increased the rate of [3H]-thymidine incorporation into DNA. The maximum stimulation was achieved at HDL concentration of 80 μg/ml and apolipoprotein A-I concentration of 20 μg/ml. To identify the target-cells of apolipoprotein A-I, we used thymidine analogue 5-ethynyl-2'-deoxyuridine (EdU) that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In addition to its role in cholesterol trafficking, Apo-A, a multifunctional protein, participates in inflammatory and immune responses [27]. It also stimulates the proliferation of monocytes, granulocytes and their progenitor cells and bone marrow MSCs [28] and supports MSC survival under stress conditions [29], which might be beneficial for hematopoiesis recovery [20]. Some studies revealed that exogenousfree Apo-A alters the characteristics of progenitor cell populations [30].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role in cholesterol trafficking, Apo-A, a multifunctional protein, participates in inflammatory and immune responses [27]. It also stimulates the proliferation of monocytes, granulocytes and their progenitor cells and bone marrow MSCs [28] and supports MSC survival under stress conditions [29], which might be beneficial for hematopoiesis recovery [20]. Some studies revealed that exogenousfree Apo-A alters the characteristics of progenitor cell populations [30].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, ApoA-I itself is a biologically active protein that exhibits many properties in the body. The regulatory effect of ApoA-I on the proliferation and stem properties of mesenchymal stromal cells is shown in Miroshnichenko [ 58 ]. However, it should be emphasized that the activity of ApoA-I was manifested at concentrations [ 57 , 58 ] three orders of magnitude higher than the concentration of the recombinant forms of ryGM-CSF-ApoA-I and ryG-CSF-ApoA-I.…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory effect of ApoA-I on the proliferation and stem properties of mesenchymal stromal cells is shown in Miroshnichenko [ 58 ]. However, it should be emphasized that the activity of ApoA-I was manifested at concentrations [ 57 , 58 ] three orders of magnitude higher than the concentration of the recombinant forms of ryGM-CSF-ApoA-I and ryG-CSF-ApoA-I. Other researchers obtained human interferon α2b (IFN) fused with ApoA-I, which showed more pronounced immunostimulatory activity, reduced hematotoxicity, and better pharmacokinetic properties compared to authentic IFN [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Highdensity lipoprotein (HDL) is a natural nanocarrier responsible for the transport of fat and other biomolecules (5). apoA-I is the major protein constituent of native HDL and interacts with scavenger receptors and the adenosine triphosphate (ATP)-binding cassette transporters ABCA1 and ABCG1, abundantly present on myeloid cells (6). On the basis of apoA-I, we developed innate immune cell-targeting nanocarriers, which we termed nanobiologics.…”
Section: Developing Nanobiologics With High Affinity For Myeloid Cellsmentioning
confidence: 99%